Female Gender as a Risk Factor for the Development of Drug-Induced Diseases - D. A. Sychev; O. D. Ostroumova; A. P. Pereverzev; A. I. Kochetkov; T. M. Ostroumova; M. V. Klepikova; E. Yu. Ebzeeva (Безопасность и риск фармакотерапии, 2021)
Gender is an important factor aﬀecting the risk of drug-induced adverse reactions in patients. According to scientiﬁc literature, the risk of drug-induced symptoms, syndromes, and diseases is 1.5–1.7 times higher in women than in men. The aim of the study was to analyse and systematise data on the factors responsible for increased risk of drug-induced diseases in women. It was demonstrated that the increased risk of complications in women following the use of certain pharmacological classes of drugs is associated with a combination of factors that aﬀect pharmacokinetics and pharmacodynamics. These factors include anatomical and physiological characteristics, speciﬁcity of enzyme and transport protein activity/expression. Women, compared to men, have higher percentage of adipose tissue and lower percentage of water in the body, which aﬀects the volume of distribution of lipophilic agents, such as opioids and benzodiazepines, resulting in their accumulation in the body. Women have a lower rate of renal excretion and elimination, as compared to men, which may lead to adverse reactions following the use of medicines with predominantly urinary excretion. Changes in the endocrine proﬁle in women taking sex steroids as replacement therapy or a contraceptive measure, as well as ﬂuctuations in endogenous sex steroids during the menstrual cycle, pregnancy, perimenopause, inﬂuence the volume of distribution, the activity of cytochrome P450 enzymes, and the glomerular ﬁltration rate, and, thus, may aﬀect the pharmacokinetics and pharmacodynamics of other medicinal products, which, in turn, aﬀect the safety of pharmacotherapy. In order to increase the safety of pharmacotherapy in women, it is necessary to consider the revealed speciﬁc pharmacokinetic and pharmacodynamic parameters of the medicine in a given group of patients when selecting the treatment regimen, including the dosage regimen and routes of administration.